Midwives On The Frontline: History Of Exposure To Covid-19 And Relationship With Anxiety - Rahmi Nurrasyidah; Lutfiana Puspita Sari (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Midwives have a high risk of being infected COVID-19 because they have a heavy workload. Midwives who work in health services also have families to protect. The threat of being exposed to COVID-19 can affect their psychological state include anxiety. This study aims to determine the relationship between a history of exposure to COVID-19 in midwives and their families with the midwife's anxiety about COVID-19. This is a cross sectional study design. Sample involved in this study was 135 midwives working in Klaten Regency. The instrument uses a questionnaire. Results of the study found that there was no significant relationship between midwife's and family's history of being exposed to COVID-19 and the midwife's anxiety about COVID-19 (p value > 0.005). It is necessary to improve the design with case controls in future studies.